Evaluation Du Coût Economique De La Dégradation Des Terres Dans La Zone Agro-Ecologique Du Centre Bénin - Akpinfa, Edouard Dossou; Kissira, Aboubakar; Akpo, Marius Afouda; Houssou, Christophe Sègbè (European Scientific Journal, ESJ, 2017)
The Agro-Ecological Zone of the Center of Benin is facing a growing degradation of agricultural land with multiple consequences at social and economic levels. This study aims to estimate the economic value of this degradation. The experimental set up is a Fisher block with corn as vegetative material. This is an arrangement of separate blocks of one factor and two levels. The first level is without fertilizer and the second with mineral fertilizer as the dose recommended by the Agricultural Management Services. Each block is a repetition and each repetition is performed by a producer on his farm. Thus, there were a total of 12 producers at a rate of 4 for highly degraded lands, 4 for those moderately degraded and 4 for low degraded lands. The evaluated agronomic parameters are related to the growth in height and circumference of the plants’ girth and the corn yield. The test shows on one hand, a drop in yield of about 50.85%, which is a monetary loss of 190,965 CFA per hectare for moderately degraded lands and about 84.41% for a monetary loss of 317,001.9 FCFA per hectare for highly degraded lands, on the other hand.